The revised Atlanta criteria more accurately reflect severity of post-ERCP pancreatitis compared to the consensus criteria. Issue 4 (May 2019) - Smeets, XJNM; Bouhouch, N; Buxbaum, J; Zhang, H; Cho, J; Verdonk, RC; Römkens, TEH; Venneman, NG; Kats, I; Vrolijk, JM; Hemmink, GJM; Otten, A; et al.
Background and objective: Post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is the most prevalent complication after ERCP with an incidence of 3.5%. PEP severity is classified according to either the consensus criteria or the revised Atlanta criteria. In this international cohort study we investigated which classification is the strongest predictor of PEP-related mortality. Methods: We reviewed 13, 384 consecutive ERCPs performed between 2012 and 2017 in eight hospitals. We gathered data on all pancreatitis-related adverse events and compared the predictive capabilities of both classifications. Furthermore, we investigated the correlation between the two classifications and identified reasons underlying length of stay. Results: The total sample consisted of 387 patients. The revised Atlanta criteria have a higher sensitivity (100 vs. 55%), specificity (98 vs. 72%) and positive predictive value (58 vs. 5%). There is a significant difference ( p  < 0.001) between the two classifications. In 124 patients (32%), the length of stay was influenced by concomitant diseases. Conclusion: The revised Atlanta classification is superior in predicting mortality and better reflects PEP severity. This has important implications for researchers, clinicians and patients. For the diagnosis of PEP pancreatitis, the consensus criteria remain the golden standard. However, the revised Atlanta criteria are preferable for defining PEP severity.